The Effectiveness of Storytelling Technique in Teaching and Learning Narrative Writing in the Malay Language - Jusoh, Zuraini (2009)
Research on the effectiveness of storytelling technique in teaching and learning narrative writing in Malay language has been done qualitatively, by using the quasi experiment nonequivalent control group design at a secondary school in Pelabuhan Klang, Selangor. As many as 66 students from Form One were chosen as the research sample, that is 32 students in the control group and 34 students in the experimental group. Both groups were given pre-test and post-test narrative writing ending with the note, “ I certainly will change”. The pre-test and post-test scores were compared to determine the effectiveness of storytelling technique in teaching and learning narrative writing in the Malay language for Form One students. From this study the result showed that, there is a significant difference between pre-test and post-test in the experimental group. This proved the effectiveness of storytelling technique in narrative writing, t (33) = 5.36, p = 0.0001, d = 0.92. The result also showed that both groups improved in narrative writing performance when t-test showed there was an increase in the control group, t (31) = 2.64, p = 0.013, d = 0.47. Even though there was an increase in scores for both groups, however there was a greater increase in the result of the experimental group (t-test d value, d = 0.92 as compared to the control group (d = 0.47). In conclusion, even though there was an increase in scores in the experimental group, but the increase was average performance only (the increase was 41.2 percent to 85.3 percent in the post-test). Even though the storytelling technique in this research did not improve narrative writing to an excellent level, but the effectiveness of the storytelling technique in teaching and learning cannot be denied. So, for further research it is recommended that stringent actions should be taken to overcome the weaknesses in this research, so that the effectiveness of the storytelling technique can be taken as an effective technique in teaching and learning.